Bean Yellow Mosaic Virus in Soybean from Argentina - Campos, Ramon E (2014)
An association of Bean yellow mosaic virus (BYMV), (genus Potyvirus), with yellow mosaic leaf symptoms on soybean in Argentina was determined by enzyme-linked immunosorbent assay, a result confirmed by transmission electron microscopy and reverse transcription-polymerase chain reaction using a degenerate primer targeting the C-terminal region of BYMV′s NIb. The sequence analysis showed that the isolate had 80.6–91.6% identities with other BYMV isolates from different strain groups, indicating that it is a strain of BYMV.